2005
DOI: 10.1128/ec.4.5.920-930.2005
|View full text |Cite
|
Sign up to set email alerts
|

The so Locus Is Required for Vegetative Cell Fusion and Postfertilization Events in Neurospora crassa

Abstract: The process of cell fusion is a basic developmental feature found in most eukaryotic organisms. In filamentous fungi, cell fusion events play an important role during both vegetative growth and sexual reproduction. We employ the model organism Neurospora crassa to dissect the mechanisms of cell fusion and cell-cell communication involved in fusion processes. In this study, we characterized a mutant with a mutation in the gene so, which exhibits defects in cell fusion. The so mutant has a pleiotropic phenotype,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
156
0
4

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 128 publications
(164 citation statements)
references
References 58 publications
(87 reference statements)
4
156
0
4
Order By: Relevance
“…In our trichogyne-fusion assay, microconidia containing a single H1-GFP-labeled nucleus were used as the male crossing partner (see materials and methods). Successful fusion between a microconidium and trichogyne of opposite mating type can be detected as a disappearance of the H1-GFP nucleus from the male cell as a consequence of its migration through the trichogyne and into the protoperithecium (Fleißner et al 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our trichogyne-fusion assay, microconidia containing a single H1-GFP-labeled nucleus were used as the male crossing partner (see materials and methods). Successful fusion between a microconidium and trichogyne of opposite mating type can be detected as a disappearance of the H1-GFP nucleus from the male cell as a consequence of its migration through the trichogyne and into the protoperithecium (Fleißner et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…However, not all N. crassa fusion mutants are affected in both germling/hyphal fusion and trichogyne-conidium fusion. For example, mutations in so, which encodes a filamentous ascomycetespecific protein, completely abolish germling and hyphal fusion in N. crassa, but trichogyne-conidium fusion is unaffected (Fleißner et al 2005); so mutants show no chemotropic interactions during germling fusion . These data indicate that N. crassa uses different molecular mechanisms for cell-cell communication and chemotropic growth that precede cell fusion during germling/hyphal fusion vs. mating during sexual reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…1B (see also Supporting information movies 1 ). Remarkably, another essential protein for CAT fusion, with unknown function, soft (SO) [17], exhibited a complementary oscillatory pattern, with a maximum intensity in one cell synchronized with the maximum of MAK-2 in the other. Fleißner et al [20] suggested that the MAK-2 peaks correspond to the receiving of a signal while the SO maxima to the sending of it (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The CATs select their partners at a distance as evidenced by their purposeful homing toward each other that becomes apparent when their separation is less than $15 mm. Genetic analyses identified a number of candidate genes whose products were required for CAT formation, homing and fusion [14][15][16][17][18][19]. Deletion of the gene encoding the MAP kinase MAK-2 resulted in cells unable to chemotropically home and fuse with other, even normal, wild-type, cells.…”
Section: Introductionmentioning
confidence: 99%
“…Formation and fusion of conidial anastomosis tubes were assayed (Fleissner et al 2005;Kim and Borkovich 2006). The ability of two strains to undergo hyphal fusion and form a heterokaryotic colony was tested (Davis and Deserres 1970;Kim and Borkovich 2004).…”
Section: Phenotypic Analysis 'mentioning
confidence: 99%